Geographical distribution of resistance to spore killer in N. crassa and N. intermedia - B. C. TURNER (Fungal Genetics Reports, 1990)
Spore killer-2 (Sk-2K) is a rare meiotic drive factor found only in four (among about 2,500) collected cultures of N. intermedia, two from Borneo, and one each from Java and Papua New Guinea (Turner et al 1987 Fungal Genet. Newsl. 34:59-62). When strains carrying Sk-2K are crossed to other N. intermedia strains, each ascus contains four viable ascospores, which carry Sk-2K, and four aborted ascospores. In some populations of N. intermedia, one third to one half of the strains collected carry a gene, tightly linked or allelic to Sk-2K, which confers full or partial resistance to killing. In crosses between Sk-2K and a resistant (r(Sk-2)) strain, each ascus contains four viable Sk-2K progeny and four (sometimes fewer) viable r(Sk-2) progeny. N. intermedia is found around the world at all longitudes sampled, but resistance to Sk-2K is found only in approximately half the globe, roughly centered in the region where Sk-2K was found.